Type V Secretion Systems: An Overview of Passenger Domain Functions - Meuskens, Ina; Saragliadis, Athanasios; Leo, Jack C.; Linke, Dirk (Frontiers in Microbiology, 2019)
Bacteria secrete proteins for different purposes such as communication, virulence functions, adhesion to surfaces, nutrient acquisition or growth inhibition of competing bacteria. For secretion of proteins, Gram-negative bacteria have evolved different secretion systems, classified as secretion systems I through IX to date. While some of these systems consist of multiple proteins building a complex spanning the cell envelope, the type V secretion system, the subject of this review, is rather minimal. Proteins of the Type V secretion system are often called autotransporters. In the simplest case, a type V secretion system consists of only one polypeptide chain with a β-barrel translocator domain in the membrane, and an extracellular passenger or effector region. Depending on the exact domain architecture of the protein, type V secretion systems can be further separated into sub-groups termed type Va through e, and possibly another recently identified subtype termed Vf. While this classification works well when it comes to the architecture of the proteins, this is not the case for the function(s) of the secreted passenger. In this review, we will give an overview of the functions of the passengers of the different autotransporter classes, shedding more light on the variety of functions carried out by type V secretion systems.